Local Wisdom Is An Identty Of Kampung Naga (Research About Potential Local Wisdom Education Tourism Destination at Kampung Naga, West Java) - Kurniasih , Erna; Retnowati (Advances in Social Sciences Research Journal, 2019)
The purpose of this research is to find out about Identity and local wisdom in Kampung Naga community that involve in their culture so that can find out and describe how local wisdom in Kampung Naga potential as educational tourism destinations based on their local wisdom. This research uses qualitative method with ethnography approach. The researcher collects the data through observation, interview that involving the community of Kampung Naga village especially Kuncen and tour guide and by documentation.The research found that local wisdom in Kampung Naga can be seen in the form of various aspects such as tradition, livelihood, ritual and rules which contain many positive values which can be sampled and use as learning materials among them: 1). loving and respecting the environment 2). mutual cooperation and togetherness 3). simplicity and equality 4). creativity 5). responsibility, consistent and principled.